Dynamic buckling of braces in concentrically braced frames - Kazemzadeh Azad, Sina; Topkaya, Cem; Bybordiani, Milad (Earthquake engineering & structural dynamics, 2018)
Axially loaded members might experience compressive forces above their static buckling capacity because of dynamic buckling under rapid shortening. Although the subject is studied in the context of engineering mechanics, it has not been thoroughly investigated in the field of earthquake engineering. Such dynamic overshoots in the compressive capacity can also be observed for braces of concentrically braced frames (CBFs) during earthquakes. Consequently, a comprehensive investigation is conducted in this study regarding the effects of dynamic buckling of braces on the seismic behavior of steel CBFs. After providing a theoretical background, recent dynamic experiments on braces and CBFs are simulated and discussed to investigate the occurrence of dynamic overshoot during these tests. Eight archetype CBFs are then designed, modeled, and subjected to a large set of ground motions to provide a quantified insight on the frequency and anticipated level of dynamic overshoot in the compressive capacity of braces during earthquakes. Results of a total of 1600 nonlinear time history analyses revealed that dynamic overshoots occur frequently in braces and affect the behavior of CBFs notably. Considerable increases are recorded in forces transmitted to other members of CBFs as a consequence of such dynamic overshoots. Importance of incorporating these dynamic overshoots in the capacity design procedure of columns, beams, and gusset plates is highlighted. Furthermore, results of a parametric study are presented and summarized in the form of a simple formula that can be used as a guide for estimating the level of dynamic overshoot.